CHC ALGORITHM FOR ANTENNA ARRAY WITH FAILED ELEMENTS OPTIMIZATION - Artyushenko, Bogdan; Shilo, Galina; Krischuk, Volodymyr (International Journal of Computing, 2014)
A new CHC based method for optimization of antenna array, with failed elements, is developed. Performances of CHC and canonical genetic algorithm are compared. Numerical results show that CHC gives better results with the same working time. To improve computational efficiency parallelization possibilities are studied.